Understanding the social barriers faced by university students with hearing loss in Singapore - Heng, Kerri Yi Ping (2017)
While Singapore has made progressive strides towards the inclusion of students with disabilities in higher education, there is a dearth of knowledge about the lived experiences of these students vis-à-vis their academic settings. This study aims to understand the social barriers faced by university students with hearing loss in Singapore. Through in-depth interviews with 11 university students with hearing loss and their immediate stakeholders – four disability support staff, one Senior Lecturer, and one student note-taker, the researcher has explored symbolic interrelationships between disclosure, reactions to disclosure, and accommodation. The physical lecture hall and the social arena of “class participation” have also been identified as key university settings that pose barriers for students with hearing loss. Lastly, the researcher examines the possibilities of an ideal mindset towards the provision of accommodations.